Measurement of ϕ(1020) meson production in fixed-target pNe collisions at √sNN = 68.5 GeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
The first measurement of ϕ(1020) meson production in fixed-target pNe collisions at √sNN = 68.5 GeV is presented. The ϕ(1020) mesons are reconstructed in their K+K− decay in a data sample consisting of proton collisions on neon nuclei at rest, corresponding to an integrated luminosity of 21.7 ± 1.4 nb−1, collected by the LHCb detector at CERN. The ϕ(1020) production cross-section in the centre-of-mass rapidity range of −1.8 < y* < 0 and transverse momentum range of 800 < pT < 6500 MeV/c is found to be σ = 182.7 ± 2.7 (stat.) ± 14.1 (syst) μb/nucleon. A double-differential measurement of the cross-section is also provided in four regions of rapidity and six regions of transverse momentum of the ϕ(1020) meson and compared with the predictions from Pythia and EPOS4, which are found to underestimate the experimental values.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" tiefgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascón, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M.D Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 17.10.2025